What to Accommodate to Develop Students' Academic Writing? Need Analysis for a Research-Based Textbook Development - Rizka Safriyani; Rakhmawati Rakhmawati; Lisanul Uswah Sadieda (IJET (Indonesian Journal of English Teaching), 2021)
The development of research-based learning proliferates throughout the world, and it depicts the growth of an academic article's publication globally. To strengthen the paper's quality, particularly in Indonesia, the students need a guideline on writing an academic article. This qualitative and quantitative research would portray the needs analysis in developing a research-based textbook in academic writing. Fifty students and thirty lecturers were involved in the interview, documentation, and survey. The result shows that the skills needed to accommodate are referencing skills, writing the research's significance, and writing the conclusion. This study also suggested nine units of an Academic Writing Textbook needed by the students to produce a good article, namely Introduction to Academic Article Writing, Strategies in avoiding plagiarism, Writing an introduction, writing a literature review, writing a research method, Presenting Findings and Discussion, Writing a conclusion, Tips on Referencing, choosing the title, and writing an abstract. These findings strengthen the previous studies, which states writing a conclusion of an academic article is challenging, particularly in the English Language Teaching context.